Toxin-mediated ribosome stalling reprograms the Mycobacterium tuberculosis proteome - Barth, Valdir C. (Nat Commun, 2019)
Mycobacterium tuberculosis readily adapts to survive a wide range of assaults by modifying its physiology and establishing a latent tuberculosis (TB) infection. Here we report a sophisticated mode of regulation by a tRNA-cleaving toxin that enlists highly selective ribosome stalling to recalibrate the transcriptome and remodel the proteome. This toxin, MazF-mt9, exclusively inactivates one isoacceptor tRNA, tRNA(Lys43-UUU), through cleavage at a single site within its anticodon (UU↓U). Because wobble rules preclude compensation for loss of tRNA(Lys43-UUU) by the second M. tuberculosis lysine tRNA, tRNA(Lys19-CUU), ribosome stalling occurs at in-frame cognate AAA Lys codons. Consequently, the transcripts harboring these stalled ribosomes are selectively cleaved by specific RNases, leading to their preferential deletion. This surgically altered transcriptome generates concomitant changes to the proteome, skewing synthesis of newly synthesized proteins away from those rich in AAA Lys codons toward those harboring few or no AAA codons. This toxin-mediated proteome reprogramming may work in tandem with other pathways to facilitate M. tuberculosis stress survival.